1970
DOI: 10.1007/bf01976581
|View full text |Cite
|
Sign up to set email alerts
|

The biological transmission of potato leafroll virus by Myzus persicae

Abstract: The ability of the green peach aphid, Myzuspersicae, to transmit potato leafroll virus after a six-hours' acquisition feeding period on leaf roll-diseased plants of Physalis floridana, followed by a feeding for different lengths of time on Chinese cabbage (Brassica pekinensis) was determined. Virus transmission was optimally efficient at about the ninth day after aphid birth. If after a one-hour acquisition feeding period on a virus source the aphids were starved for different numbers of days at 4~ the efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1971
1971
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…An exhaustive list of photometric measurements of ρ Pup was reported by Moon & van Antwerpen (2009). Ponsen (1963), Eggen (1956), and Hipparcos (ESA 1997) data are the most suitable for a detailed analysis. Data were obtained in different passbands: Ponsen's measurements were taken through a blue filter, Eggen's through a yellow filter, and those of Hipparcos in the wide H p passband.…”
Section: ρ Pupmentioning
confidence: 99%
See 1 more Smart Citation
“…An exhaustive list of photometric measurements of ρ Pup was reported by Moon & van Antwerpen (2009). Ponsen (1963), Eggen (1956), and Hipparcos (ESA 1997) data are the most suitable for a detailed analysis. Data were obtained in different passbands: Ponsen's measurements were taken through a blue filter, Eggen's through a yellow filter, and those of Hipparcos in the wide H p passband.…”
Section: ρ Pupmentioning
confidence: 99%
“…The variability of ρ Pup ≡ HD 67523 ≡ HR 3185, one of the brightest (V = 2.88) δ Sct stars, was first reported by Cousins (1951) and then clearly demonstrated by Eggen (1956) and Ponsen (1963). An accurate value of the pulsational period (P = 0.14088143 d) was determined from photometric data spanning fifty-two years (Moon & van Antwerpen 2009).…”
Section: Introductionmentioning
confidence: 96%
“…The detected minima were separated by about 0.82 d. This prompted de Kort (1955) to do photometry with the Riverview Observatory (Australia) plates. He found that the orbit is highly eccentric and the true orbital period amounts to about 3.28 d. This finding was confirmed by Ponsen (1956). In a survey of spectra of southern eclipsing binaries at Mount Stromlo Observatory, the star was found to be SB2 by Popper (1966).…”
Section: Appendix A: Notes On Individual Starsmentioning
confidence: 76%
“…The star V703 Sco (HD 160589) is a HADS with periods of P 1 = 0.14996 d (ν 1 = 6.66844 d −1 ), P 2 = 0.11522 d (ν 2 = 6.67905 d −1 ), which might be due to the fundamental and first overtone modes, with a ratio of 0.768, and (Ponsen, 1961;Oosterhoff, 1966;Koen, 2001). The rotational velocity is v sin i = 16 km s −1 and the spectral type is A9V (Houk, 1982).…”
Section: V703 Sco and 1 Monmentioning
confidence: 99%